Treatment of pharmaceutical industry wastewater for water reuse in Jordan using hybrid constructed wetlands - Al-Mashaqbeh, Othman; Alsalhi, Layal; Salaymeh, Lana; Dotro, Gabriela; Lyu, Tao (Elsevier, 2024)
Developing cost-efficient wastewater treatment technologies for safe reuse is essential, especially in developing countries simultaneously facing water scarcity. This study developed and evaluated a hybrid constructed wetlands (CWs) approach, incorporating tidal flow (TF) operation and utilising local Jordanian zeolite as a wetland substrate for real pharmaceutical industry wastewater treatment. Over 273 days of continuous monitoring, the results revealed that the first-stage TFCWs filled with either raw or modified zeolite performed significantly higher reductions in Chemical Oxygen Demand (COD, 58 %–60 %), Total Nitrogen (TN, 32 %–37 %), and Phosphate (PO4, 46 %–64 %) compared to TFCWs filled with normal sand. Water quality further improved after the second stage of horizontal subsurface flow CWs treatment, achieving log removals of 1.09–2.47 for total coliform and 1.89–2.09 for E. coli. With influent pharmaceutical concentrations ranging from 275 to 2000 μg/L, the zeolite-filled hybrid CWs achieved complete removal (>98 %) for ciprofloxacin, ofloxacin, erythromycin, and enrofloxacin, moderate removal (43 %–81 %) for flumequine and lincomycin, and limited removal (<8 %) for carbamazepine and diclofenac. The overall accumulation of pharmaceuticals in plant tissue and substrate adsorption accounted for only 2.3 % and 4.3 %, respectively, of the total mass removal. Biodegradation of these pharmaceuticals (up to 61 %) through microbial-mediated processes or within plant tissues was identified as the key removal pathway. For both conventional pollutants and pharmaceuticals, modified zeolite wetland media could only slightly enhance treatment without a significant difference between the two treatment groups. The final effluent from all hybrid CWs complied with Jordanian treated industry wastewater reuse standards (category III), and systems filled with raw or modified zeolite achieved over 95 % of samples meeting the highest water reuse category I. This study provides evidence of using hybrid CWs technology as a nature-based solution to address water safety and scarcity challenges.
Keywords: Modified zeolite; Micropollutants; Nature-based solution; Removal pathways; Tidal flow wetland; Treatment wetlands